Optimization Design of Polar-LDPC Concatenated Scheme Based on Deep Learning. (June 2020) - Wang, Xiumin; Li, Jun; Chang, Hong; He, Jinlong
Abstract: In 5G communication system, because of incomplete polarization of the polar codes, the performance of the polar codes is poor at low and medium SNR. Concatenating the polar codes and low-density parity-check codes (LDPC), the Polar-LDPC concatenated scheme improves decoding performance. Although the decoding performance of the Polar-LDPC concatenated scheme is improved, the decoding delay is increased compared with the non-concatenated scheme. In order to solve this problem, we propose a Polar-LDPC concatenated scheme based on deep learning by paralleling multiple neural networks. The decoding delay of the polar codes assisted by the neural network is reduced in the proposed Polar-LDPC concatenated scheme. The experiment results show that the proposed concatenated scheme can reduce time complexity compared with the non-concatenated scheme under the same code length.